The association between diabetes status and latent-TB IGRA levels from a cross-sectional study in eastern China - Chen, Cheng; Hu, Xinsong; Shao, Yan; Song, Honghuan; Li, Guoli; Lu, Wei; Martinez, Leonardo; Xu, Jianfang; Zhu, Limei (Frontiers in Cellular and Infection Microbiology, 2023)
Background: There is a debate regarding the sensitivity of the QuantiFERON-TB GOLD-In-Tube (QFT) among people with diabetes and prior studies have shown heterogeneous results. We evaluated whether the QFT TB antigen was modified among persons with differing diabetes status and other related risk factors. Methods: A cross-sectional study of 5302 people was conducted to screen latent tuberculosis infection (LTBI) in eastern China. The QFT assay was performed as an indicator of LTBI. Fasting plasma glucose (FPG) was collected from each participant; the definition of diabetes followed the guidelines from the American Diabetes Association. Participants were classified into normoglycemia, pre-diabetes, undiagnosed diabetes, and previously diagnosed diabetes to evaluate the relationship between the QFT TB antigen and distinct diabetes status. Results: TB antigen values from the QFT were statistically different among participants with differing diabetes status (P=0.008). Persons with undiagnosed diabetes had a higher TB antigen value (0.96 ± 0.20) than persons with normoglycemia (0.50 ± 0.02, P<0.05). However, the TB antigen values demonstrated no significant difference among the four different diabetic groups when stratified by the standard cutoff for the QFT (P=0.492 for positive group and P=0.368 for negative group). In a linear regression model, we found FPG, age, and smoking were positively associated with QFT TB antigen value (P=0.017, P<0.001, and P<0.001). Conclusions: Diabetes status had little influence on the level of QFT TB antigen response among IGRA positive persons. However, FPG, old age, and smoking were important risk factors for increasing levels of QFT TB antigen.